(untitled) (The Accounting Educators’ Journal, 2011)
Lehman Brothers, Inc. was one of the very early casualties of the 2008-09 worldwide financial crisis becoming the largest bankruptcy of a U.S. financial institution. Prior to its demise, Lehman Brothers periodically employed an accounting technique known as Repo 105 for its financial reporting of certain transactions involving repurchase agreements. The Repo 105 accounting allowed Lehman to temporarily reduce its debt levels during periods that included financial statement preparation. The purpose of this case is to summarize the accounting for Lehman Brothers’ Repo 105 transactions, present some classroom discussion points, and provide student review questions related to accounting and financial reporting issues underlying the Repo 105 transactions.